2022
DOI: 10.1155/2022/1819606
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Effect of Core Stability Training on Correction and Surface Electronic Signals of Paravertebral in Adolescent Idiopathic Scoliosis

Abstract: Objective. To observe the effect of 12-week core stability training on Cobb angle and the ratios of AEMG (averaged EMG) and IEMG (integral EMG) of paravertebral electromyography in thoracic and lumbar segments in adolescent idiopathic scoliosis (AIS) patients and offer a practical-based evidence for the rehabilitation treatment for AIS patients. Methods. 31 AIS female middle school students were randomly divided into an exercise group ( n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Our meta-analysis found that CS exercises had a very shortterm efect to reduce Cobb's angle and improve lumbar muscle strength in AIS patients compared with conventional training in three studies [7,25,26]; however, the subgroup analysis showed no signifcant improvement [16,27,28]. Te subgroup analysis of the efects in Cobb's angle was divided into thoracic and lumbar segments.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Our meta-analysis found that CS exercises had a very shortterm efect to reduce Cobb's angle and improve lumbar muscle strength in AIS patients compared with conventional training in three studies [7,25,26]; however, the subgroup analysis showed no signifcant improvement [16,27,28]. Te subgroup analysis of the efects in Cobb's angle was divided into thoracic and lumbar segments.…”
Section: Discussionmentioning
confidence: 82%
“…CS exercises may increase the strength of spinal muscles, improve the quality of life, and relieve pain in adolescents with AIS [19] and could correct the bad posture of scoliosis patients, which may be related to the balance of the electromyographic activities (convex concave side) of paravertebral muscles in AIS patients [7]. CS exercises were more efective than traditional exercises alone in the correction of vertebral rotation and reduction of pain in adolescent idiopathic scoliosis [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1091 relevant literature were retrieved, and a total of 19 articles were finally included. 19,20,22,23,[26][27][28]30,[35][36][37][38][39][40][41][42][43][44][45] The literature inclusion process is shown in Figure 1.…”
Section: Results Literature Screening Resultsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%